Quality Assessment of the Blended Learning in Higher Education Using the Modified HEdPERF Instrument - Dao Thanh Binh; Ngoc Tran Thi Bich; Nguyen Hoang Lan; Trinh Thu Thuy; Galina Barysheva; Lam Tran Si (Emerging Science Journal, 2025)
The objective of this study is to introduce the HEdPERF instrument as a means to objectively assess the impact of various factors on the quality of blended learning, particularly focusing on student satisfaction. In the study, both quantitative and qualitative methods were utilized to analyze the results of the survey conducted online with 662 students and face-to-face interviews with 180 students from different faculties at Hanoi University of Science and Technology, covering students from their first to fifth years. The results show that factors including Academic and Non-Academic aspects, IT Facilities and Infrastructure, Access and Learning Organization, as well as the characteristics of the training major of the students and their academic year, impact the quality of blended learning, which requires a need to balance traditional in-person classroom instruction and online learning. The novelty of this study lies in the selection and modification of dimensions and items from Abdullah's HEdPERF instrument to evaluate factors affecting the quality of higher education services. This approach can be applied to assess various learning models or the quality of educational services offered by higher education institutions while considering the characteristics of different academic disciplines and the students' year of study. Doi: 10.28991/ESJ-2025-SIED1-04 Full Text: PDF